The Relationship between Job Characteristics and the Quality of Work Life of the Gampong Government - Irin Riamanda; Risana Rachmatan; Eka Dian Aprilia; Faisal (IJIP : Indonesian Journal of Islamic Psychology, 2022)
A gampong, generally known as a village, is a legal community unit with territorial boundaries and is led by a keuchik or other name who has the right to carry out their household affairs. In its implementation, there are obstacles felt by the village government while working, such as the condition of the work environment that results in low quality of work life. In contrast, the quality of work life must be conditioned by the organization so that the welfare and productivity of employees go well, one way to improve the quality of work life is to apply job characteristics model. Job characteristics are job attributes that have a motivational function for employees. Therefore, research is needed to determine the relationship between job characteristics and the quality of work life of the village government. This study used a quantitative approach with purposive sampling data collection techniques. The research sample comprised 297 village governments in Banda Aceh and Aceh Besar. Data was collected using the Job Diagnostic Survey scale and the quality of work-life scale. The results of this study explained that the hypothesis is accepted where the significance value is p = 0.000, which meant that there was a relationship between job characteristics and the quality of working life of the village government. That is, the higher the job characteristics, the higher the quality of work life of the village governments. This study found that the job characteristics and quality of work life were in the medium category. The results also found that the quality of work life in the Banda Aceh village government was higher than that of the Aceh Besar village government. This is due to clear working hours and higher salaries, in addition to weekly supervision from the sub-district on the performance of the Banda Aceh village government.